2004
DOI: 10.1016/j.ejvs.2003.11.010
|View full text |Cite
|
Sign up to set email alerts
|

Aneurysmal Hypertension and its Relationship to Sac Thrombus: A Semi-qualitative Analysis by Experimental Fluid Mechanics

Abstract: Thrombus has a significant effect on the intraaneurysmal lumen itself and causes localised hypertension with high intraluminal pressures. The differences between the sac wall/luminal pressures may affect regional aneurysm wall biomechanics, but needs further study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 14 publications
(2 reference statements)
0
4
0
Order By: Relevance
“…On the other hand, there is still some concern regarding the protective role of ILT, since many authors who evaluated in vivo the influence of ILT on intraluminal pressure transmission reported that the presence of ILT fails to reduce the transmission of intraluminal pressure on the AAA wall, consequently leaving the risk of AAA rupture unaffected. 18,19 The above has been reported to hold true even in thrombosed aneurysms. [20][21][22][23][24][25][26] The mechanical properties of ILT that are typically utilized in computational patientspecific AAA models are derived from population mean parameters for ILT material characteristics.…”
Section: Role Of Peak Wall Stress (Pws)mentioning
confidence: 76%
“…On the other hand, there is still some concern regarding the protective role of ILT, since many authors who evaluated in vivo the influence of ILT on intraluminal pressure transmission reported that the presence of ILT fails to reduce the transmission of intraluminal pressure on the AAA wall, consequently leaving the risk of AAA rupture unaffected. 18,19 The above has been reported to hold true even in thrombosed aneurysms. [20][21][22][23][24][25][26] The mechanical properties of ILT that are typically utilized in computational patientspecific AAA models are derived from population mean parameters for ILT material characteristics.…”
Section: Role Of Peak Wall Stress (Pws)mentioning
confidence: 76%
“…But a glycerol/water mixture has a markedly higher density (1172 kg/m 3 ) than both blood (1060 kg/m 3 ) and water (1000 kg/m 3 ). 19 Since our results suggest that redirection of flow is a more important factor for displacement forces than shear stress, a similar density is more important than a similar viscosity to mimic the in vivo situation. 10 Sideways movement was limited by the stent graft's fixed anchoring to the strain gauge load cells.…”
mentioning
confidence: 70%
“…On a recent study, Polzer et al [114] have found that ILT fissures locally increase the mechanical stress in the underlying wall up to a 30% which could possibly cause AAA rupture. In addition, in vivo measurements of intraluminal pressure pointed out that the presence of ILT did not significantly reduce the transmission of intraluminal pressure on the AAA wall [115,116]. From a mechanical point of view, ILT is usually considered as a homogeneous incompressible hyperelastic solid [110,117,118].…”
Section: Influence Of Ilt On Peak Wall Stressmentioning
confidence: 99%